PENGARUH PERCEIVED USEFULLNESS, PERCEIVED EASE OF USE, TRUST, DAN PERCEIVED RISK TERHADAP KEPUTUSAN PENGGUNAAN APLIKASI HALODOC DI KOTA DENPASAR - Ni Putu Leonny Indriani; Gusti Ayu Sugiati; Luh Putu Indiani (Fakultas Ekonomi Universitas Warmadewa, 2023)
This research aims to determine the effect of perceived usefullness, perceived ease of use, trust, and perceived risk on the decision to use the Halodoc application. The population in this research are all Halodoc application users in Denpasar City. This research uses a non-probability sampling method, namely the incidental sampling method, with the ancient rao formula obtained a total sample of 96 people. Collecting data using a questionnaire with linear regression. The research results illustrate that perceived usefulness, perceived ease of use, trust and perceived risk simultaneously have a positive and significant effect on decisions to use the Halodoc application. Partially Perceived usefulness has a positive and significant effect on decisions to use the Halodoc application, Perceived ease of use has a positive and significant impact on decisions to use the Halodoc application, Trust has a positive and significant impact on decisions to use the Halodoc application, Perceived risk has a positive and significant impact on decisions use on the Halodoc application. The Halodoc application is expected to maximize the usefulness of the application for users, one of which is by increasing the practicality of payments.